Circ-ADAM9 Promotes High Glucose-Induced Retinal Pigment Epithelial Cell Injury in DR via Regulating miR-338-3p/CARM1 Axis - Zeyu Liang; Chengzhe Lu; Tingting Feng; Xiang Gao; Yongfang Tu; Wenchao Yang; Yipeng Wang (Journal of Ophthalmology)
Background. Circular RNAs (circRNAs) have been reported to be involved in the regulation of retinal pigment epithelial (RPE) cell injury and are closely related to the development of diabetic retinopathy (DR). More research is needed to confirm the role and mechanism of circ-ADAM9 in DR progression. Methods. High glucose (HG)-induced RPE cells (ARPE-19) were used to mimic the hyperglycemia condition. The expression of circ-ADAM9, microRNA (miR)-338-3p, and coactivator-associated arginine methyltransferase 1 (CARM1) was measured using quantitative real-time PCR. Cell proliferation and apoptosis were determined using MTT assay, EdU assay, and flow cytometry. The protein expression of apoptosis markers and CARM1 was examined by the western blot analysis. Also, MDA level and SOD activity were determined to assess cell oxidative stress. In addition, the interaction between miR-338-3p and circ-ADAM9 or CARM1 was confirmed by dual-luciferase reporter assay and RIP assay. Results. The expression of circ-ADAM9 was upregulated in DR patients and HG-induced ARPE-19 cells. Silenced circ-ADAM9 could promote proliferation and inhibit inflammation, apoptosis, and oxidative stress in HG-induced ARPE9 cells. In terms of mechanism, circ-ADAM9 could sponge miR-338-3p to upregulate CARM1. The inhibitory effect of circ-ADAM9 knockdown on HG-induced ARPE9 cell injury could be reversed by an miR-338-3p inhibitor. As a target of miR-338-3p, CARM1 knockdown could alleviate HG-induced ARPE9 cells’ injury, and its overexpression also could reverse the negatively regulation of miR-338-3p on HG-induced ARPE9 cell injury. Conclusion. Circ-ADAM9 contributed to HG-induced ARPE9 cell injury by regulating miR-338-3p/CARM1 axis, which provided effective targets for DR treatment.